P1433Prevalence and location of residual leaks following percutaneous left atrial appendage occlusion: the importance of 3D transesophageal echocardiography. (18th June 2020) - Lopes, J; Teixeira, R; Campos, D; Saleiro, C; Sousa, J; Puga, L; Ribeiro, J; Silva, J; Goncalves, L
Abstract: Background: The left atrial appendage (LAA) shape and size are very variable, and incomplete appendage closure or persistent leaks around the device are common following device placement. Limited studies reported the rate of peri-device leaks (PDL) after percutaneous left atrial appendage closure, and the impact of 3D transesophageal echocardiography (3D-TEE) on the detection of those leaks. Aim To describe the rate and location of leaks 1 month after percutaneous closure of the LAA, with and without the use of 3D-TEE. Methods: A cohort study of consecutive patients (P) who were submitted to a percutaneous LAA closure with success in one interventional cardiology centre, between May 2010 and October 2018, were included. Clinical and echocardiography data were recorded and analysed. Two groups were created: Group A (GA) included patients until August 2015 submitted to 2D TEE on follow up (N= 48) versus Group B (GB), which was composed of patients submitted to 3D-TEE after August 2015 (N= 76). Results: A total of 124 P had an in-hospital admission for LAA closure, with control TEE 1 month after the procedure. Mean age was 73 ± 7 years old, with 62.9% male patients. The procedure was guided by TEE (52%) or intra cardiac echocardiography (ICE) (48%).Transeptal puncture was preferred (95% of the procedures). The most used device was Amulet (62%) vs ACP (23%) and Watchman (15%). In the follow up TEE, 20% of patients had only 1 leak and 2% had 2 leaks. Of the detected leaks, 31% were considered minor (< 1 mm), 35% moderate (1-3 mm) and 34% major (> 3 mm). Patients with leaks had a larger LAA diameter (22 ± 4 mm vs. 17 ± 3 mm,  P = 0.01). Of the detected leaks, 50% were located in the superior portion of the device, 23% were located in the inferior portion, 8% in the posterior portion and 8% in the lateral portion. In GA the rate of leaks was 14% vs 24.5% in GB, with differences also when specified the size of the leak –  minor (GA 2% vs GB 8.8%), moderate (GA 8% vs GB 8.1%) and major (GA 4% vs GB 7.6%). Conclusion: The use of 3D echocardiography, 1 month after successful percutaneous LAA closure, augmented the rate of detection of device leaks. It remains to be studied the clinical impact of this finding.